Mechanical behaviors and rupture processes of a typical granitic stratum - Xiaofang Nie; Dong Wang; Song Yuan; Liangpu Li; Zhilong Zhang; Zidong Fan; Qin Zhou; Meng Wang; Li Ren (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
Granitic veins (GVs) have a significant influence on the mechanical responses of tunnels excavated in granitic strata. Distinguishing the mechanical properties of host granites (HGs), GVs and vein-granite interfaces (VGIs) is critical. For this, this paper analyzed the mechanical behaviors and rupture processes of typical HG, GV, and VGI samples under uniaxial compression condition. For the rocks studied, although the linear axial stress‒strain relation can be identified and the deformation modulus can be determined, the transverse deformation developed nonlinearly with axial stress. As a result, the instantaneous Poisson's ratio increases continuously and may even exceed 0.5, making it extremely difficult to accurately determine the Poisson's ratio. In addition, the studied GV samples were found to be significantly brittle, indicating that large-scale GVs cannot be ignored when assessing rockburst hazards in granitic strata with brittle GVs. In terms of the rupture process, the HG and GV samples were gradually damaged by the formation of small-scale cracks and then ruptured by large cracks formed from small-scale cracks, whereas the VGI samples ruptured along large cracks with significant energy release. By examining the characteristic stress thresholds of these three granites, it is noted that the crack closure stress σcc exceeds both the crack initiation stress σci and the crack damage stress σcd for the HG and VGI samples. The transverse damage to a tested sample appears to be significantly greater than the axial damage, which is essentially related to the rock grain size and grain size distribution.